Jewish daily life in Germany, 1618-1945 - Kaplan, Marion A. (Oxford University Press, 2005)
A study of Jewish life in Germany from 1618 until 1945, this work investigates the details of daily living, the homes and neighbourhoods in which Jews lived, their families and friendships, religious practices and feelings, as well as their educations and occupations.